Transition‐Metal‐Based Cocatalysts for Photocatalytic Water Splitting. Issue 7 (23rd April 2022) - Zhao, Hui; Jian, Liang; Gong, Ming; Jing, Mengyang; Li, Haixia; Mao, Qinyi; Lu, Tongbin; Guo, Yinxin; Ji, Rong; Chi, Wenwen; Dong, Yuming; Zhu, Yongfa
Abstract : Recently, semiconductor‐based photocatalytic water splitting has been extensively studied as a promising strategy for converting solar energy into carbon‐neutral and clean H2 fuel. However, the lack of sufficient active sites for surface redox reactions generally results in unsatisfactory photocatalytic water splitting performances over semiconductors. For this problem, cocatalyst provides an encouraging solution and is of great significance in improving photocatalytic performance. Noble metals and their derivatives are mostly utilized as efficient cocatalytic components, but their scarcity and expensiveness severely hamper large‐scale applications. Thereby, the utilization of noble‐metal‐free cocatalysts has aroused immense research attention. Owing to the facile availability, low cost, large abundance, high stability, and efficient performance, transition‐metal‐based materials have been developed as desirable candidates in the photocatalytic water splitting water splitting process. This review gives an outline of some recent advances in the active transition‐metal‐based water splitting cocatalysts. First, the fundamentals of transition‐metal‐based cocatalysts are presented, including the classification, function mechanisms, loading methods, modification strategies, and design considerations. Second, the various cases of depositing reduction cocatalysts, oxidation cocatalysts, and reduction–oxidation dual cocatalysts for water splitting are further discussed. Finally, the crucial challenges and possible research directions of transition‐metal‐based cocatalysts for photocatalytic water splitting are proposed. Abstract : Herein, the fundamentals of transition‐metal‐based cocatalysts in photocatalytic water splitting are provided, including the categories, cocatalytic roles, deposition methods, influence factors, modification strategies, and design considerations. Furthermore, based on the types and roles of transition‐metal‐based cocatalysts, their recent developments in assisting photocatalytic water splitting are discussed, involving the performance, functions, and synergistic mechanisms.